Effects of partial preheated dough on its frozen characteristics: Baking, water mobility, thermal, and microstructural properties. Issue 4 (7th April 2021) - Yuan, Yirong; Hong, Tingting; Ma, Yongshuai; Xu, Dan; Zhang, Huang; Jin, Yamei; Wu, Fengfeng; Xu, Xueming
Abstract: Background and objectives: Flour heat treatment is commonly used to improve dough and bread quality. This study creatively proposed applying partial preheated dough (PPHD) to frozen dough and evaluated bread characteristics and its internal mechanism systematically. Findings: Results suggested that moderate PPHD level presented higher specific volume, softer hardness, more appealing brown crust color and more uniform texture of frozen dough bread. Moisture status analysis showed that PPHD restricted the mobility of overall water molecules and the migration from bound water to semi‐bound water. DSC and RVA results suggested that the inter‐ and intramolecular association of starch granules, leading to abundant formation of hydrogen bonds, strengthened the gluten matrix network. Besides, gelatinized starch granules in PPHD served as a paste to promote the cross‐linking of starch and gluten, which was observed by SEM. Conclusions: Partial preheated dough inhibited ice recrystallization by restricting water migration and formed a highly networked starch–gluten structure that delayed its destruction during freezing. Significance and novelty: This study demonstrated obvious improvement of PPHD on frozen dough quality and further explained the mechanism systematically. Moreover, the method was innovative, simple, and easy to operate, so it could help to promote the development of the frozen dough industry.